TECHNOLOGIES FOR USING SOFTWARE PACKAGES TO TEACH DIGITAL RESOURCE MODELING IN HIGHER EDUCATION - Siradjev Salokhiddin Negmatovich (American Journals, 2023)
In this article, special attention is paid to how, when choosing didactic and technical means of education, these tools help to organize the activities of students in order to know in this or that field of knowledge. Also, within the framework of an active approach to education, the concept of "activity" is often associated with the concept of "knowledge", that is, it is argued that in order to form knowledge as an element of the consciousness of an individual, it is necessary to organize cognitive activity of the appropriate type, level and size.
Keywords: Information, visualization modeling, teaching methods, forms and tools, software packages, etc.